Heritage, urban form and spatial resignification in the production of sustainable Olympic legacies: an urban design analysis of the Rio de Janeiro Olympic Games - Renata Latuf de Oliveira Sanchez (Built Heritage)
Abstract The Olympic Games have been associated with many urban transformation projects throughout their history, often focusing on city expansion. Recent sustainability concerns, however, constitute a pressing challenge, with the regeneration of central areas fulfilling a key role in existing urban agendas. In this paper, the legacy of the Rio 2016 Olympic Games at two proposed centralities was analysed, namely, the Olympic Park, intended as a future neighbourhood to the west of the city, and Porto Maravilha (PM), an urban project aimed at revitalizing a central, historical area of the city. By comparing the Olympic Park and the first provided areas in PM, in terms of selecting urban design criteria through qualitative in loco assessments, this paper focused on analysing the impacts of urban forms and heritage on the consolidation of these two centralities, as well as encouraging social interaction and integration into the city. The analysis results indicated that urban design attributes such as human-scaled, mixed-use, context-based urban spaces could interfere with social interaction and the usability of spaces. Moreover, the repurposing of heritage buildings contributed to urban cohesion for legacy transformation. Hence, novel insights into urban design and heritage could become important for future editions of the Olympics so that host cities may fulfil their sustainability agendas.